Influence of Growing Substrate Preparation on the Biological Efficiency of Pleurotus ostreatus - Francesco De Mastro; Andreina Traversa; Francesco Matarrese; Claudio Cocozza; Gennaro Brunetti (Horticulturae, 2023)
Pleurotus ostreatus is one of the most cultivated mushrooms worldwide. It is a lignocellulolytic fungus cultivated on different substrates, whose more common raw material is straw. The present study investigated the biological efficiency of Pleurotus ostreatus as affected by the different age of straw and the growing media preparation process in four production cycles. The content of organic carbon significantly decreased during the growing media preparation, while the content of total nitrogen, moisture, and ash, as well asthe pH value, showed an opposite trend. The first production cycle was characterized by the highest total and soluble sugar content. A dramatic reduction in soluble sugars was recorded at the end of the preparation of the growing media, regardless of the production cycle, while the total sugars were slightly reduced during the production cycle. The microbial population was significantly influenced by the growing media preparation, while only bacteria were slightly influenced by the straw’s age. In contrast, cellulase activity significantly increased in the old straw, while an opposite trend was observed for pectinase activity. The β-glucosidase activity was influenced only by the growing media preparation. As expected, cluster analysis showed that the microbial community changed in each phase of growing media preparation. Finally, the biological efficiency of Pleurotus ostreatus decreased from 26.28% to 15.49% with increasing age of the straw, which may presumably be ascribed to the higher content of sugars in fresh straw compared to the older ones. Therefore, fresh straw should be used to prepare the growing media of Pleurotus ostreatus in order to increase its biological efficiency.